Exploring the landscape of livestock ‘facts’ - Salmon, Gareth R.; Macleod, M.; Claxton, J.R.; Pica-Ciamarra, U.; Robinson, Timothy P.; Duncan, Alan J.; Peters, Andrew R. (Elsevier, 2020)
The role of livestock in supporting human well-being is contentious, with different perceptions leading to polarised opinions. There is increasing concern about the health and environmental impacts of a high rate of consumption of livestock products in high-income countries. These concerns are heightened by an increase in consumption in middle-income countries. On the other hand, livestock support the livelihoods of many people, particularly in low income countries. The benefits of livestock for poor livestock keepers are multiple, including the important role livestock play in supporting crop production in mixed systems, in supplying nutrients and income, and in fulfilling cultural roles. In addition livestock can provide resilience against economic and climate shocks. In view of these apparent positive and negative impacts, the role of livestock in human wellbeing is highly contested, with arguments 'for' or 'against' sometimes distorted by vested interests or misinterpretation of evidence. The Livestock Fact Check project, undertaken by the Livestock Data for Decisions community of practice, has investigated several ideas concerning livestock commonly taken as 'fact'. By exploring the provenance of these 'facts' we highlight their importance and the risks of both misinterpreting them or using them out of context. Despite the diversity of the livestock sector resulting in equally diverse viewpoints, the project calls for participants in the livestock discourse to adopt a nuanced appreciation of global livestock systems. Judgement of livestock's role in global sustainable diets should be based on clear and well-interpreted information.